Optical Fiber Sensor for Soil Moisture Detection - Zulkapli, Nuralia; Adnan, Nurul Nadia (Enhanced Knowledge in Sciences and Technology, 2025)
Soil moisture measurement plays a vital role in various sectors such as agriculture, environmental monitoring, and geotechnical engineering. This research aims to develop and evaluate a fiber optic displacement sensor for soil moisture detection, emphasizing the effects of lateral offset and the sensor's interaction with various soil types. Clay and medium sand soils were examined at moisture contents of 15%, 27%, and 38%, utilizing the evanescent wave effect, where light traveling through the fiber interacts with the surrounding soil, causing detectable changes in optical power. The findings reveal that the sensor is more sensitive to moisture in clay soil, with a higher sensitivity of -0.0135 dBm/% compared to medium sand at -0.0074 dBm/%. Furthermore, the study identifies the lateral offset at which the sensor performs optimally for each soil type. In conclusion, fiber optic sensors prove to be a reliable and efficient tool for soil moisture detection, with significant potential for use in precision agriculture and environmental monitoring, while highlighting the importance of optimizing sensor designs based on soil characteristics.